Investment Arbitration - Abi Farraj, Wajih (2020)
Investment arbitration is an alternative dispute resolution mechanism that solves investment disputes outside the scope of state courts. This mechanism has been recognized in the Lebanese law where the Lebanese legislator adopted a liberal approach toward arbitration. Throughout this paper, the Lebanese domestic and international arbitration laws are explained along with an analysis of investment arbitration and investment treaties. This paper aims to highlight the importance of arbitration in general, and to demonstrate the effectiveness of investment arbitration. For this purpose the paper is supported by a real life investment arbitration case between Lebanon and a foreign investor that took place at the International Center for Settlement of Investment Disputes. An analysis of the whole mechanism is held at the end of the paper, and a critical analysis of investment treaties shows the disadvantages that might be associated with this mechanism when dealing with developing countries.